Recondensation level of repetitive sequences in the plant protoplast nucleus is limited by oxidative stress - Ondřej, Vladan (Oxford University Press, 2010)
Protoplast cultures are remarkable examples of plant cell dedifferentiation. The state of dedifferentiation is evidenced by changes in cell morphology, genome organization, as well as by the capability of protoplasts to differentiate into multiple types of cells (depending on the type of the stimulus applied). The first change in the genome structure is connected with large-scale chromatin decondensation, affecting chromocentres involving various types of these repetitive sequences. This paper describes not only the de- and recondensation of satellite DNA type I and 5S rDNA repetitive sequences, but it also compares the recondensation level of chromatin with the levels of oxidative stress which were decreased by using an antioxidant, as well as the capabilities of the antioxidative systems within protoplasts, during the first 72 h of their culture. It is demonstrated that the treatment of protoplasts with ascorbic acid not only decreased the level of oxidative stress but also positively stimulated the expression of the ascorbate peroxidase and catalase. It also led to a greater recondensation of the chromatin (when compared to the untreated protoplasts); in addition, it supported cell proliferation. It is concluded that large-scale genome relaxation is more directly connected with oxidative stress than with large changes in the expression of genes; and further, that its recondensation is related to the start of (as well as the level of) protection by the antioxidative systems.